Association between mass media exposure and HIV testing uptake in Cameroon. - Roger Antabe; Yujiro Sano; Daniel Amoak (PLOS Global Public Health)
In sub-Saharan African countries, mass media is critical in disseminating health information, including the need for HIV testing. Yet, in Cameroon, there is a dearth of studies examining how exposure to mass media is effective in the uptake of HIV testing. Using the 2018 Cameroon Demographic and Health Survey, we examined the association between exposure to mass media and HIV testing among sexually active women (n = 12,619) and men (n = 5,607). Our findings revealed a generally low uptake of HIV testing although more women (78%) have ever tested for HIV compared to men (67%). Adjusting for demographic, socioeconomic, and psychosocial factors, we found for both women and men their exposure at least once a week to the Internet (aOR = 1.57, p<0.001 for women; aOR = 1.76, p<0.001 for men), print media (aOR = 1.59, p<0.05 for women; aOR = 2.04, p<0.001 for men), radio (aOR = 1.34, p<0.01 for women; aOR = 1.57, p<0.001 for men), and television (aOR = 1.74, p<0.001 for women; aOR = 1.94, p<0.001 for men) was significantly associated with a higher likelihood of testing for HIV compared to their counterparts with no exposure at all. Our findings underscore the importance of further integrating mass media in HIV messaging in Cameroon as the country aims to achieve UNAIDS target 95-95-95 by 2023.